* What role does surgery play in the modern day management of non-variceal upper gastrointestinal bleeding?. (13th March 2011) - Jairath, V; Logan, R; Hearnshaw, S; Kahan, B; Travis, S; Murphy, M; Palmer, K
Abstract : Introduction: Combinations of endoscopic, pharmacological and radiological intervention appears to have reduced the need for surgery in non-variceal upper gastrointestinal bleeding (NVUGIB), for what was once a condition primarily managed by surgeons. The place of surgery in today's management of NVUGIB remains poorly characterised. Methods: We examined the clinical characteristics, sequence of intervention and outcomes of NVUGIB in a nationwide study, by analysing patients coming to surgery in the 2007 national audit of Acute Upper Gastrointestinal Bleeding1 . Results: The study recruited 6, 750 patients. Only 1.9% (127/6750) underwent surgery. The mean age was 69.4 (SD 15) years, 60% (75/127) male, with median of 1 co-morbid illnesses. Indications for surgery were uncontrolled bleeding/high risk stigmata of haemorrhage in 82% (104/127), peritonitis/perforation in 12% (15/127), malignancy in 4% (5/127), and other indications in 9% (12/127). Surgical procedures were oversew or under-run of an ulcer in 65% (83/127), partial gastrectomy in 9% (12/127), excision of an ulcer with vagotomy/pyloroplasty (2%) and other procedure in 20%. Surgery was performed outside of normal working hours in 54% (69/127), lead by a consultant surgeon in 71% (90/127) with a consultant anaesthetist in 64% (81/127). A median of 1 endoscopy was performed prior to surgery and 5% (6/127) had also undergone mesenteric angiography, with apparently successful embolisation in 33% (2/6) of cases. Mortality following surgery was 30% (38/127). Post-operative complications occurred in 65% (82/127). Compared to patients managed non-surgically, patients requiring surgery were older (mean 69.4yrs vs. 64.3 yrs, p<0.0001), more likely to have been shocked (66% vs. 36% p<0.0001), transfused a greater number of red cells (median 9 units vs. 4 units, p<0.0001) and have a higher complete Rockall score (median 6 vs. 4, p<0.0001). AUROC analysis showed that the complete Rockall score usefully predicted the need for surgery (AUC 0.74, 95% CI 0.7-0.78), but the clinical Rockall score did not (AUC 0.613, 95%CI 0.56-0.67). Conclusion: Modern day management of NVUGIB rarely requires surgical intervention. Given the high mortality and complication rates of patients following surgery, its role and timeliness needs re-evaluation in the hope of improving outcomes following AUGIB.